Antibiotics for Aspiration Pneumonia in Neurologically Impaired Children. Issue 7 (20th November 2019) - Thomson, Joanna; Hall, Matt; Ambroggio, Lilliam; Berry, Jay G; Stone, Bryan; Srivastava, Rajendu; Shah, Samir S
Abstract : OBJECTIVE: To compare hospital outcomes associated with commonly used antibiotic therapies for aspiration pneumonia in children with neurologic impairment (NI). DESIGN/METHODS: A retrospective study of children with NI hospitalized with aspiration pneumonia at 39 children's hospitals in the Pediatric Health Information System database. Exposure was empiric antibiotic therapy classified by antimicrobial activity. Outcomes included acute respiratory failure, intensive care unit (ICU) transfer, and hospital length of stay (LOS). Multivariable regression evaluated associations between exposure and outcomes and adjusted for confounders, including medical complexity and acute illness severity. RESULTS: In the adjusted analysis, children receiving Gram‐negative coverage alone had two‐fold greater odds of respiratory failure (odds ratio [OR] 2.15; 95% CI: 1.41‐3.27), greater odds of ICU transfer (OR 1.80; 95% CI: 1.03‐3.14), and longer LOS [adjusted rate ratio (RR) 1.28; 95% CI: 1.16‐1.41] than those receiving anaerobic coverage alone. Children receiving anaerobic and Gram‐negative coverage had higher odds of respiratory failure (OR 1.65; 95% CI: 1.19‐2.28) than those receiving anaerobic coverage alone, but ICU transfer (OR 1.15; 95% CI: 0.73‐1.80) and length of stay (RR 1.07; 95% CI: 0.98‐1.16) did not statistically differ. For children receiving anaerobic, Gram‐negative, and P. aeruginosa coverage, LOS was shorter (RR 0.83; 95% CI: 0.76‐0.90) than those receiving anaerobic coverage alone; odds of respiratory failure and ICU transfer rates did not significantly differ. CONCLUSIONS: Anaerobic therapy appears to be important in the treatment of aspiration pneumonia in children with NI. While Gram‐negative coverage alone was associated with worse outcomes, its addition to anaerobic therapy may not yield improved outcomes. Abstract :